MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNINGI (PBL) PADA MATERI TEKANAN ZAT - Meyko Adjilahu; Muhammad Yusuf; Tirtawaty Abdjul (Jambura Physics Journal, 2021)
The Classroom Action Research (CAR) is aimed at improving students learning outcomes by using Problem Based Learning (PBL) model on Substance Pressure material in grade VIIIA of SMP Negeri 1 Dulupi. This Classroom Action Research was carried out from October 2019 to March 2020 in the even semester of 2019-2020 with the number of students who were subject to action as many as 25 people and carried out in 2 cycles. the result of the analysis showed that students learning outcomes from cycle I to cycle II has increased. In cycle I, students’ mastery learning only at 64%, with 16 total students who were completed and 9 students incomplete. After being given action in cycle II, there was an increase to 84%, with 21 total students who were completed and 4 students incomplete. Based on these data, it is concluded that Problem Based Learning (PBL) model can improve students learning outcomes